Managerial decision-making during the COVID-19 pandemic and its impact on the sustainability initiatives of Canadian foodservice businesses. Issue 2 (4th March 2023) - Robinson, Emily; McAdams, Bruce; Somogyi, Simon; Thomas-Francois, Kimberly
ABSTRACT: COVID-19 had a major impact on the Canadian foodservice sector. Like most countries, the pandemic in Canada resulted in various periods of lockdown. The pandemic placed great strain on many establishments and had a major impact on the pre-COVID-19 sustainability initiatives of the Canadian foodservice sector. The purpose of this study was to observe managerial decision-making in Canadian foodservice businesses during lockdown and reopening, focusing on the impact of those decisions on pre-COVID-19 sustainability initiatives. We linked the outcomes to the theory of decision-making by objection during times of crises. This study used semi-structured interviews over a two-month period in mid-2020 with three Canadian foodservice establishments. Our results showed that decision-making impacted the environmental sustainability initiatives in foodservice establishments by imposing a throwaway culture for food and personal protective equipment. The pandemic also impacted social and economic initiatives, created higher operation costs, a complexity of government intervention and the managing of mental health. This study showed that the COVID-19 pandemic provided an opportunity to develop theories of managerial decisions during crises and disasters that are natural, versus human-based crises, with pandemics situated between those two concepts. Future research could investigate the impact of decision-making on other initiatives within foodservice businesses.